Material Salvation: Healing, Deliverance, and “Breakthrough” in African Migrant Churches in Germany - Währisch-Oblau, Claudia (Global Pentecostal and Charismatic Healing, 2011)
Migrants from West and Central Africa, mostly Ghana and Nigeria, arrived in Germany in the 1980s. Migrant pentecostal churches are missionary bridgeheads with evangelistic calling, or reverse missions, towards German society. Migrants participate, as producers as well as consumers, in transnational communication networks, and migration drives the multi-directional, global circulation of ideas. Migrants believe the visible world in which they live is enclosed in an invisible world that influences everything in the visible world. Healing and prosperity are not blessings beyond salvation but express material salvation. Problems can only be solved by “supernatural breakthrough,” through “spiritual warfare” (“authority prayer” or “prayer of command,” since spoken words are powerful)—ideas of African as much as American origin. Evangelism is not communication of a message, but power encounter or power evangelism, as healing and deliverance fuel missionary outreach towards non-Christians. Migrants tailor evangelism methods to German sensibilities, for instance hosting musical Gospel concerts.
paid